CORROSION PROTECTION OF UNDERWATER BODY OF WAGB'S - Parker, E. L. (1965)
This report summarizes the results of various test programs of corrosion protection used on the icebreaker hulls (WAGB). It discusses the present corrosion rates encountered with no corrosion protection and presents possible approaches to corrosion protection of the class ship.